Human intrabony defect regeneration with micrografts containing dental pulp stem cells: A randomized controlled clinical trial. (15th June 2018) - Ferrarotti, Francesco; Romano, Federica; Gamba, Mara Noemi; Quirico, Andrea; Giraudi, Marta; Audagna, Martina; Aimetti, Mario
Abstract: Aim: The goal of this study was to evaluate if dental pulp stem cells (DPSCs) delivered into intrabony defects in a collagen scaffold would enhance the clinical and radiographic parameters of periodontal regeneration. Materials and Methods: In this randomized controlled trial, 29 chronic periodontitis patients presenting one deep intrabony defect and requiring extraction of one vital tooth were consecutively enrolled. Defects were randomly assigned to test or control treatments which both consisted of the use of minimally invasive surgical technique. The dental pulp of the extracted tooth was mechanically dissociated to obtain micrografts rich in autologous DPSCs. Test sites ( n = 15) were filled with micrografts seeded onto collagen sponge, whereas control sites ( n = 14) with collagen sponge alone. Clinical and radiographic parameters were recorded at baseline, 6 and 12 months postoperatively. Results: Test sites exhibited significantly more probing depth (PD) reduction (4.9 mm versus 3.4 mm), clinical attachment level (CAL) gain (4.5 versus 2.9 mm) and bone defect fill (3.9 versus 1.6 mm) than controls. Moreover, residual PD < 5 mm (93% versus 50%) and CAL gain ≥4 mm (73% versus 29%) were significantly more frequent in the test group. Conclusions: Application of DPSCs significantly improved clinical parameters of periodontal regeneration 1 year after treatment.